KNOWING GOD FROM THE PERSPECTIVES OF ʿILM AL-KALĀM AND TAṢAWWUF - Anwa Dueramae; Novia Safitri Dalimunte; Muhammad Salman Qureshi; Ahmad Rafie; Yusuph Dauda Gambari (Yayasan Dinamika Literasi Jambi, 2026)
The study of divinity constitutes a fundamental foundation in Islamic teachings, addressed through various scholarly disciplines, particularly kalam (Islamic theology) and tasawwuf (Islamic mysticism). Kalam emphasizes a rational and argumentative approach in understanding the existence, attributes, and actions of God, whereas tasawwuf focuses on inner realization and spiritual experience in knowing the Divine. This article aims to examine the concept of knowing God from the perspectives of kalam and tasawwuf, as well as to analyze the relationship between the two in constructing a comprehensive understanding of faith. This study employs a qualitative method with a library research approach, analyzing both classical and contemporary sources in the fields of kalam and tasawwuf. The findings reveal that kalam plays a significant role in establishing the rational foundations of faith through the concepts of tawhid, iman, and the divine attributes, while tasawwuf serves as a complementary dimension by introducing the experiential aspects of ihsan, muraqabah, and ma‘rifatullah. The relationship between iman (faith) and ihsan (spiritual excellence) emerges as the primary point of convergence between kalam and tasawwuf, where faith is not only understood conceptually but also embodied in moral and spiritual consciousness. Thus, the integration of kalam and tasawwuf is essential to ensure that the understanding of God does not remain confined to a rational-dogmatic level, but rather develops into a profound spiritual realization that shapes ethical conduct and holistic religious behavior.